Satisfaction with and reliability of in-hospital video-EEG monitoring systems in epilepsy diagnosis – A German multicenter experience. Issue 9 (September 2021) - Willems, Laurent M.; Baier, Hartmut; Bien, Christian G.; Bösebeck, Frank; Dümpelmann, Matthias; Hamer, Hajo M.; Kellinghaus, Christoph; Knake, Susanne; Schreiber, Melanie; Staack, Anke Maren; Surges, Rainer; Tergau, Frithjof; et al.
Highlights: Satisfaction with video-electroencephalography-monitoring systems (VEMS) at German epilepsy centers is low. Diagnosis is jeopardized in approximately every 10th patient due to hardware or software errors. Improvements in system stability and customer service are urgently needed. Abstract: Objective: To analyze satisfaction with and reliability of video-electroencephalography-monitoring systems (VEMS) in epilepsy diagnostics. Methods: A survey was conducted between December 2020 and January 2021 among German epilepsy centers using well-established customer satisfaction (CS) and quality assurance metrics. Results: Among 16 participating centers, CS with VEMS was low, with only 13% of customers actively recommending their system. Only 50% of users were satisfied with the overall performance of their VEMS, and a low 18% were satisfied with the manufacturer's customer service. User interface, software stability, lack of regular updates, and missing customer-oriented improvements were reported as frequent problems jeopardizing diagnosis in approximately every 10th patient. The greatest potential for improvement was identified for software and hardware stability as well as customer service. Conclusion: Satisfaction with VEMS and their customer service was low, and diagnostics were regularly affected by software or hardware errors. Even if this can be partly explained by the technical complexity of VEMS, there is an urgent need for improvements with regard to the reliability and durability of system components as well as signal synchrony and data management. Significance: This analysis highlights low consumer satisfaction of users with VEMS and uncovers frequent problems and potential for improvement.